4(5z-1)-5(z+2)=4(z+1)

Simple and best practice solution for 4(5z-1)-5(z+2)=4(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5z-1)-5(z+2)=4(z+1) equation:


Simplifying
4(5z + -1) + -5(z + 2) = 4(z + 1)

Reorder the terms:
4(-1 + 5z) + -5(z + 2) = 4(z + 1)
(-1 * 4 + 5z * 4) + -5(z + 2) = 4(z + 1)
(-4 + 20z) + -5(z + 2) = 4(z + 1)

Reorder the terms:
-4 + 20z + -5(2 + z) = 4(z + 1)
-4 + 20z + (2 * -5 + z * -5) = 4(z + 1)
-4 + 20z + (-10 + -5z) = 4(z + 1)

Reorder the terms:
-4 + -10 + 20z + -5z = 4(z + 1)

Combine like terms: -4 + -10 = -14
-14 + 20z + -5z = 4(z + 1)

Combine like terms: 20z + -5z = 15z
-14 + 15z = 4(z + 1)

Reorder the terms:
-14 + 15z = 4(1 + z)
-14 + 15z = (1 * 4 + z * 4)
-14 + 15z = (4 + 4z)

Solving
-14 + 15z = 4 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
-14 + 15z + -4z = 4 + 4z + -4z

Combine like terms: 15z + -4z = 11z
-14 + 11z = 4 + 4z + -4z

Combine like terms: 4z + -4z = 0
-14 + 11z = 4 + 0
-14 + 11z = 4

Add '14' to each side of the equation.
-14 + 14 + 11z = 4 + 14

Combine like terms: -14 + 14 = 0
0 + 11z = 4 + 14
11z = 4 + 14

Combine like terms: 4 + 14 = 18
11z = 18

Divide each side by '11'.
z = 1.636363636

Simplifying
z = 1.636363636

See similar equations:

| 2(4)+5(0)=15 | | r+13.12=1 | | 16t^2+128t+320=0 | | -5(7-10x)= | | 8-3.8k=-4 | | -16t+128t+320=0 | | 5x+5y+5z=300 | | 5y-13=7y-19 | | -32-3.5f=-17 | | -2x+3y=40 | | 1.2y-1.8=7.8 | | 10+3x=2x+9 | | b.3-6=-2 | | .75z-1=.25(z+8) | | 3x^2=7-20x | | 12y-11=y^2 | | 2(x-3)-3(5x-2)=1 | | 16x^2=56x-49 | | 2x+-15x+6-6=10 | | t^2+44+15t=0 | | 3x-4=-x+44 | | 3(x-2)-3=5x-1 | | 6x-9y=-27 | | 7n-28=3(3n-7) | | (5b-4)(6b-6)= | | 5b-4*6b-6= | | 7-7x=92-42x | | 9.-4+3=15 | | -7x+5+10=3x-7-2x | | u.5+6=2 | | 5(y+2)=20 | | 5b-20=18+3b |

Equations solver categories